Semitransparent superoleophobic coatings with low sliding angles for hot liquids based on silica nanotubes. Issue 3 (16th December 2015) - Li, Bucheng; Zhang, Junping; Gao, Ziqian; Wei, Qingyun
Abstract : Semitransparent superoleophobic coatings with low sliding angles for hot liquids are successfully prepared by fabrication of silica nanotubes on glass slides, and then modification with 1 H, 1 H, 2 H, 2 H -perfluorodecyltrichlorosilane. Abstract : Semitransparent superoleophobic coatings with low sliding angles for hot liquids are successfully prepared by fabrication of silica nanotubes (SNTs) on glass slides, and then modification with 1 H, 1 H, 2 H, 2 H -perfluorodecyltrichlorosilane. The SNT layers are formed by spray-coating a homogeneous dispersion of polydimethylsiloxane (PDMS)-modified multiwalled carbon nanotubes (MWCNTs) onto glass slides followed by calcination to remove MWCNTs, the templates. The successful fabrication of SNTs and the superoleophobic coatings are confirmed by scanning electron microscopy, transmitting electron microscopy, X-ray photoelectron spectroscopy and investigation of the wetting behavior of n -decane on the coatings, etc. The microstructures of the SNT layers have great influence on superoleophobicity of the coatings, which are controllable by simply regulating the diameter of MWCNTs and the concentrations of MWCNTs and PDMS. The superoleophobic coatings feature high contact angles and low sliding angles for various liquids (such as water, toluene, n -hexadecane, n -decane, etc. ), excellent superoleophobicity for hot liquids and good transparency.